2014
DOI: 10.1590/0103-6440201300143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment of Fiberglass Posts on Bond Strength to Root Dentin

Abstract: This study evaluated the influence of the surface treatments of fiberglass posts on bond strength to root dentin using push-out test. Forty bovine incisor roots were endodontically treated. The surface of the fiberglass posts (Exacto #2, Angelus) were treated using 4 different protocols (n=10): Control - 70% ethanol for 1 min; 37% phosphoric acid for 1 min; 10% hydrofluoric acid for 1 min; and 24% hydrogen peroxide for 1 min. After a silane coupling agent was applied for 1 min and all posts were cemented using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
2
17
0
4
Order By: Relevance
“…In this study four post and core surface treatments (alcohol or hydrogen peroxide, with or without silane) were proposed. According to the results, there was no significant difference between groups, corroborating findings in the literature ( 16 , 20 ). Thus, the first hypothesis was accepted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study four post and core surface treatments (alcohol or hydrogen peroxide, with or without silane) were proposed. According to the results, there was no significant difference between groups, corroborating findings in the literature ( 16 , 20 ). Thus, the first hypothesis was accepted.…”
Section: Discussionsupporting
confidence: 90%
“…The epoxy matrix is substantially incapable of reacting with the monomers of the resin cement. Thus, the post surface treatment becomes essential, because it will partially remove the epoxy resin matrix, exposing the glass fibers so that they can receive the silanization ( 13 , 16 , 18 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the two post systems with respect to their ability to reduce the risk of root fracture and have described the best techniques and protocols for use of posts, including post length and diameter and adhesive system. These studies have used different methods, such as application of oblique load and cyclic load, but all results converge positively to the same conclusion: the use of glass-fiber posts reduces the risk of root fracture, thus increasing the success of restoration 5,7,[9][10][11][12][13][14] . However, many professionals who advocate the use of cast metal posts and cores raise the question of how copings for metal-ceramic crowns cemented to glass-fiber posts rebased with composite resin would behave under tensile stress.…”
Section: Introductionmentioning
confidence: 69%
“…Highly cross-linked epoxy resins with high degree of conversion constitute the main [86,[121][122][123][124]. The application of ascorbic acid is dependent on the increasing duration of exposure to the antioxidant [124].…”
Section: Effect Of Surface Treatment Of Glass Fiber Posts On Bond Strmentioning
confidence: 99%
“…The application of ascorbic acid is dependent on the increasing duration of exposure to the antioxidant [124]. Other examples are the use of ethanol [70,86], antioxidants such hesperidin, sodium ascorbate or rosmarinic acid [123]. Recently, a study of use of polidopamina at the post surface was found to be effective in improving the bond strength between resin cements and fiber posts without damaging the surface of the posts [57].…”
Section: Effect Of Surface Treatment Of Glass Fiber Posts On Bond Strmentioning
confidence: 99%